2022
DOI: 10.4235/agmr.22.0054
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Muscles on Bone Metabolism—with a Focus on Myokines

Abstract: Skeletal muscles and bones, the largest tissues in the body of a non-obese person, comprise the musculoskeletal system, which allows mobility and protects internal organs. Although muscles and bones are intimately related throughout life, observations during development and aging and in human and animal disuse models have revealed the synchronization of tissue mass such that muscle phenotype changes precede alterations in bone mineral density and strength. This review discussed that mechanical forces, which ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 101 publications
0
8
0
Order By: Relevance
“…Besides its role in force generation, the skeletal muscle is an endocrine organ that communicates with other bodily systems through myokines, molecules with pluripotent effects that are synthesized and released by active skeletal myocytes [47][48][49]. Myokines influence important physiological processes at musculoskeletal, metabolic, neural, vascular, and immunological levels [49][50][51][52]. A reduced expression of several myokines has been found in muscle biopsies from critically ill patients [53], in whom a lower FNDC5/irisin ratio (precursor/myokine) has been independently associated with mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Besides its role in force generation, the skeletal muscle is an endocrine organ that communicates with other bodily systems through myokines, molecules with pluripotent effects that are synthesized and released by active skeletal myocytes [47][48][49]. Myokines influence important physiological processes at musculoskeletal, metabolic, neural, vascular, and immunological levels [49][50][51][52]. A reduced expression of several myokines has been found in muscle biopsies from critically ill patients [53], in whom a lower FNDC5/irisin ratio (precursor/myokine) has been independently associated with mortality.…”
Section: Discussionmentioning
confidence: 99%
“…[51] Additionally, various drugs that block the myostatin-activin pathway, an upstream pathway of muscle atrophy, have been developed to inhibit muscle protein breakdown in situations of anabolic resistance. [52] Studies in humans have established clinical evidence showing that older adults and individuals with chronic diseases require greater protein intake to overcome anabolic resistance. [46]…”
Section: Mechanism Of Muscle Protein Synthesisbreakdownmentioning
confidence: 99%
“…32,33 2.2 | Muscle as a "secondary periosteum" for bone regeneration Over the past few years, several studies have demonstrated that the surrounding muscle plays a key role in inducing osteogenesis. 9,[34][35][36] Historically, muscle has been viewed as a common site for heterotopic ossification that occurs either because of physical trauma or genetic disorders. 37,38 However, in recalcitrant fracture healing or distraction osteogenesis, bone formation commonly occurs nearby the surrounding muscle tissue.…”
Section: Remodeling Phasementioning
confidence: 99%
“…Over the past few years, several studies have demonstrated that the surrounding muscle plays a key role in inducing osteogenesis 9,34–36 . Historically, muscle has been viewed as a common site for heterotopic ossification that occurs either because of physical trauma or genetic disorders 37,38 .…”
Section: Clinical Challengementioning
confidence: 99%